(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The study presents the development of an improved technology for fish patties based on fish mince with the addition of pumpkin puree as a functional ingredient. The feasibility of pumpkin application was substantiated due to its content of β-carotene and pectin substances. An experimental formulation of fish patties with pumpkin was developed, along with a technological scheme using poaching as a heat treatment method to preserve nutritional value.